ANTIBACTERIAL ACTIVITY OF SPICES AGAINST MULTIPLE DRUG RESISTANT PSEUDOMONAS AERUGINOSA ISOLATED FROM POULTRY WASTE WATER - SADHANA JAISWAL; DEEPALI RAJWADE; DIKSHA KHARE; SHRIJAL KUMAR SHARMA; ALKA KAUSHIK (The Bioscan, 2024)
Conventionally spices have been widely used as flavoring agents, colorant, preservatives, food additives and medicinal purposes worldwide. The present work aimed to find out the antimicrobial activity of natural spices on multi-drug resistant Pseudomonas aeurigenosa isolated from poultry waste water. Anti-bacterial potentials of four spices extracts cinnamon, clove, black pepper and long pepper) were tested against Pseudomonas aeurigenosa isolated from poultry waste water.The highest inhibition zone was observed with long pepper (32mm). Assessment of anti-bacterial activity of common spices against other MDR bacteria could be applied for prevention & mitigation of diseases.